Effect of nonlinear inductor behavior on the performance of interleaved power factor correction - Liu, Yitao. (2013)
Power factor correction (PFC) circuit becomes increasingly popular due to the strict power quality requirement imposed by standards on power electronic systems above 75 W. Interleaved boost inductor topology in PFC is able to reduce EMI noise and boost inductor magnetic flux volume. This paper proposes a comprehensive modeling of an interleaved PFC with the consideration of the performance of nonlinear input filtering inductor. The Jiles-Atherton (J-A) model has been applied to investigate the nonlinear inductor behavior in the interleaved PFC as a part of input filter. Simulation results were verified using experimental data.